On Characterizations of Weighted Harmonic Bloch Mappings and Its Carleson Measure Criteria - Munirah Aljuaid; M. A. Bakhit (Journal of Function Spaces)
For α>0, several characterizations of the α-Bloch spaces of harmonic mappings are given. We also obtain several similar characterizations for the closed separable subspace. As an application, we give relations between BHα and Carleson’s measure.